1997
DOI: 10.1007/bf02488972
|View full text |Cite
|
Sign up to set email alerts
|

Minimum sizes for remnant and transplanted livers in rats

Abstract: Abstract:Our new technique of hepatectomy in rats, avoiding inferior vena cava constriction, revealed that 5%-10% of the total liver is the minimum required volume for remnant liver, a smaller amount than previously reported. The characteristic histological findings of remnant liver in perioperative death are marked hepatocytosis and hepatocyte apoptosis, and extensive hepatocyte necrosis with sinusoid congestion, all of which are thought to be caused by hyperendotoxemia and mitochondrial energy crisis. Partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 25 publications
1
71
1
Order By: Relevance
“…to a liver/BW ratio of 3.5, is 7-8 days. This duration is in agreement with prior experience with this surgical model [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…to a liver/BW ratio of 3.5, is 7-8 days. This duration is in agreement with prior experience with this surgical model [18][19][20][21][22][23].…”
Section: Discussionsupporting
confidence: 91%
“…As per the protocol first described by Higgins and Andersen in 1931 [18][19][20][21][22][23], 3/4 liver resections were carried out (on day 0) on one half (N = 24) of the animals. Briefly, while the animals were under isoflurane anesthesia, a midline incision was made, followed by complete liberation of all liver ligaments to allow the ligation of the pedicles of the median and left lateral lobes i.e.…”
Section: Liver Injury (Li) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatic arteries and the portal veins were dissected and the abdomen was then closed. ii) the 90% partial hepatectomy group (n=24); a 90% partial hepatectomy was performed according to a new technique described by Kubota et al (24), which was modified from the original procedure established by Higgins and Anderson (25). It was reported that all of the 90% hepatectomy rats survived using this technique (17,26).…”
Section: Methodsmentioning
confidence: 99%
“…Using this technique for 90% PHx carries a high risk of causing outflow obstruction or massive bleeding. (2) The vessel-oriented technique, which Kubota et al [47] introduced in 1997. In their study, ligation of the portal vein and hepatic artery was performed prior to ligation of the respective hepatic vein with a piercing suture, and then, the individual liver lobe was resected without the risk of bleeding and compressing the inferior vena cava.…”
Section: Surgical Modelsmentioning
confidence: 99%